Rhinonomics: a biodiversity center in the cradle of human kind in support of a legalised rhino horn trade - McCormack, Duane Allan (My University, 2014)
A fading legacy Through the intensive investigation of the rhino trade, the thesis proposes the development of a biodiversity center to serve as a research, education, training and enforcement facility which will support a legalized rhino horn trade. The relationship between architecture and nature. In so doing, it questions whether architecture can effectively facilitate the conservation of our spectacular wildlife through and ecological approach to brief, site and context. The thesis promotes and architecture that is respectful of its natural surroundings. An architecture that provides occupants with facilities that are conducive to the conservation of endangered species.
Keywords: Architecture and socitety--South Africa; Rhinoceros horn Industry--South Africa; Wildlife conservation--South Africa; Architectural design--Social aspects